Ageing and gastrointestinal sensory function: altered colonic mechanosensory and chemosensory function in the aged mouse. (19th January 2016) - Keating, Christopher; Nocchi, Linda; Yu, Yang; Donovan, Jemma; Grundy, David
Abstract : Key points: Remarkably little is known about how age affects the sensory signalling pathways in the gastrointestinal tract despite age‐related gastrointestinal dysfunction being a prime cause of morbidity amongst the elderly population High‐threshold gastrointestinal sensory nerves play a key role in signalling distressing information from the gut to the brain. We found that ageing is associated with attenuated high‐threshold afferent mechanosensitivity in the murine colon, and associated loss of TRPV1 channel function. These units have the capacity to sensitise in response to injurious events, and their loss in ageing may predispose the elderly to lower awareness of GI injury or disease. Abstract: Ageing has a profound effect upon gastrointestinal function through mechanisms that are poorly understood. Here we investigated the effect of age upon gastrointestinal sensory signalling pathways in order to address the mechanisms underlying these changes. In vitro mouse colonic and jejunal preparations with attached splanchnic and mesenteric nerves were used to study mechanosensory and chemosensory afferent function in 3‐, 12‐ and 24‐month‐old C57BL/6 animals. Quantitative RT‐PCR was used to investigate mRNA expression in colonic tissue and dorsal root ganglion (DRG) cells isolated from 3‐ and 24‐month animals, and immunohistochemistry was used to quantify the number of 5‐HT‐expressing enterochromaffin (EC) cells. Colonic and jejunal afferent mechanosensory function was attenuated with age and these effects appeared earlier in the colon compared to the jejunum. Colonic age‐related loss of mechanosensory function was more pronounced in high‐threshold afferents compared to low‐threshold afferents. Chemosensory function was attenuated in the 24‐month colon, affecting TRPV1 and serotonergic signalling pathways. High‐threshold mechanosensory afferent fibres and small‐diameter DRG neurons possessed lower functional TRPV1 receptor responses, which occurred without a change in TRPV1 mRNA expression. Serotonergic signalling was attenuated at 24 months, but TPH1 and TPH2 mRNA expression was elevated in colonic tissue. In conclusion, we saw an age‐associated decrease in afferent mechanosensitivity in the mouse colon affecting HT units. These units have the capacity to sensitise in response to injurious events, and their loss in ageing may predispose the elderly to lower awareness of GI injury or disease. Key points: Remarkably little is known about how age affects the sensory signalling pathways in the gastrointestinal tract despite age‐related gastrointestinal dysfunction being a prime cause of morbidity amongst the elderly population High‐threshold gastrointestinal sensory nerves play a key role in signalling distressing information from the gut to the brain. We found that ageing is associated with attenuated high‐threshold afferent mechanosensitivity in the murine colon, and associated loss of TRPV1 channel function. These units have the capacity to sensitise in response to injurious events, and their loss in ageing may predispose the elderly to lower awareness of GI injury or disease.